Formation of edible soybean and soybean-complex protein films by a cross-linking treatment with a new Streptomyces transglutaminase - Su, Guocheng (Array, 2007)
Soybean protein isolate (SPI) was used in the investigation of the formation of edible protein films through an enzymatic cross-linking method with a purified microbial transglutaminase (MTG) produced from a new effective strain Streptomyces sp. WZFF.L-M1 preserved in our laboratory, followed by the addition of glycerol and suitable heating and drying treatments. Cheaper partially-purified skimmed soybean protein powder (SSP) and whey protein isolates (WPI) were used as the substitutes partially replacing the expensive SPI products, and purified β-lactoglobulin was taken as the positive control of WPI. As a result, the three alternatives could also form highly efficient edible films under the optimal operation conditions. The films made with SPI alternatives, about 50 µm thin, had homogenous network structures, without any holes by direct observation with the naked eye.